Recruitment to organised crime - Iain W. Long (Cardiff University, Cardiff Business School, 2013)
Organised crime is unique within the underground economy. Unlike individual criminals, criminal organisations can substitute between a variety of inputs; chiefly labour and effort. This paper considers the effect of several popular anti-crime policies in such an environment. Using a profit maximisation framework, I find that certain policies may cause the organisation to reduce its membership in favour of more intensive activity. Others may lead to increases in membership. Consequently, policies designed to reduce the social loss suffered as a result of criminal activities may actually increase it. Results prove robust to differences in hiring practices on the part of the criminal organisation.
Keywords: J24; J28; K42; 330; Organised crime; Crime policy; Occupational choice.